The effect of crushed eggshell on concrete pavement block behaviour as a replacement of fine aggregate - Raja Abdul Aziz , Raja Mohamad (2015)
In s modern world now, many countries are going to develop due to the population growth. Malaysia is also one of the develop country and the construction will growth in the future. Chicken's egg is one of the waste material that contribute to the to the environmental problem. In order to reduce the problem, reuse the eggshell as a replacement material in concrete is a good solution to overcome all the problem. Eggshell fine grains obtained by crushing the shells have been established to be good accelarator for cement-bound material and this would be useful for road construction work at the peak of rainy seasons for reducing setting time of stabilized road pavement. However this should be achieved not at the expense of other vital properties of the stabilized matrix. This is part of the effort in adding value to agricultural materials which probably cause disposal problem. This study is therefore aimed at determining the suitability of using egg shell as partial replacement for fine aggregates in highway concrete structures. A cubes of size 65 mm x 100 mm x 210 mm with different percentages by volume were made. Crushed egg shell are added in 2.5, 5, 7.5, 10% with other concrete components in the right measurement appropriate in making concrete pavement block. Slump test, UPV test, rebound hammer test, water absorption test and compressive strength test of the concrete are determined and compared. Compressive strength test was carried out on the concrete pavement block at three levels of curing: 1, 7, 28 days.